Hi All,
I am working on the exercise questions of book The Lambda calculus. One of the questions that I am stuck is proving the following: Show that the application is not associative; in fact, x(yz) not equals (xy)z
Here is what I have worked on so far:
Let x = λa.λb. ab
Let y = λb.λc. bc
Let z = λa.λc. ac
(xy)z => ((λa.λb. ab) (λb.λc. bc)) (λa.λc. ac)
=> (λb. (λb.λc. bc) b) (λa.λc. ac)
=> (λb.λc. bc) (λa.λc. ac)
=> (λc. (λa.λc. ac) c)
x(yz) => (λa.λb. ab) ((λb.λc. bc) (λa.λc. ac))
=> (λb. ((λb.λc. bc) (λa.λc. ac)) b)
=> (λb. (λc. (λa.λc. ac) c) b)
Is this correct?
Please help me understand.
Regards, darkie